Estudo de catalisadores de cobre suportados para a reação de oxidação preferencial do CO - Maciel, Cristhiane Guimarães (2010)
The CO preferential oxidation reaction (PROX-CO) has been widely studied in last few years. Aiming H2 purification for proton-exchange membrane cells (PEMFC) use, the main role of the PROX-CO reaction should be reduce the CO contained in reformed gas to an acceptable level of CO concentration that do not provoke deactivation of Pt electrocatalyst. The search for substitutes for noble metals like Pt and Au, the first catalysts tested in PROX reaction, has been the subject of several studies. Among the proposed new solid, the Cu-O-Ce have received considerable attention. These catalysts have been shown be active and selective for PROX-CO in a temperature range that is appropriate for application in PEMFC cells and are materials of low cost. The metal-support interface of Cu-O-Ce system favors the CO oxidation reaction and some properties as metallic dispersion, particle size and morphology are determinants for the better performance of these catalysts. Therefore, in this present work, xCuO/CeO2 and xCuO/CeO2-Al2O3 catalyst (where x is the copper loading) were synthesized, characterized and tested in the CO preferential oxidation reaction. The effects of metal content, support composition, support preparation method and catalysts preparation method were evaluated. Experimental results showed that the metallic content influences the catalytic performance and the catalyst with 1% of copper content was the most active and selective for the PROX-CO. That catalyst also showed the best performance at lower temperature reaction. The study of the effect of support nature in the PROX-CO reaction showed that the strong interaction copper-ceria is a determining factor for the good performance of the catalysts. With alumina or ceria/alumina supports, the metal-support interaction is weaker and, in consequence, the catalysts were less active and selective. The preparation method study of ceria support showed that morphologic characteristics from its synthesis lead to different results of catalytic activity. The catalyst preparation method was important to catalytic activity results. The solids prepared by impregnation and citrate method were more active and selective than others. Although the catalysts synthesized by the deposition-precipitation and co-precipitation methods have also been active for the PROX-CO.